1987
DOI: 10.1021/ef00002a010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water and hydrogen partial pressures during direct liquefaction in catalyzed systems with a low solvent-to-coal ratio

Abstract: Illinois No. 6 bituminous coal with small concentrations of coal-derived solvent was subjected to hydroliquefaction in batch reactors to which substantial amounts of water were sometimes added. The reactions were catalyzed by 0.1% molybdenum on mf coal, added as a water-soluble salt. It was shown previously that a substantial water partial pressure, at fixed hydrogen partial pressure, increases coal conversion in uncatalyzed systems. The present work investigated the effect of added water in catalyzed systems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…One option for increasing catalyst activity and reducing costs would be to use catalysts in which metals are dispersed as either water-or oil-soluble liquids (Derbyshire and Hager, 1994;Ruether et al, 1987;Zhan and Givens, 1999;Demirel and Givens, 2000a), allowing the metals to deposit and interact directly on coal surfaces. Dispersed catalysts are reported to give higher liquid yields and require lower catalyst loadings than do supported catalysts Givens, 1998, 2000a, b;Ni et al, 1994).…”
Section: Reducing Capital Costs With Improved Catalystsmentioning
confidence: 99%
“…One option for increasing catalyst activity and reducing costs would be to use catalysts in which metals are dispersed as either water-or oil-soluble liquids (Derbyshire and Hager, 1994;Ruether et al, 1987;Zhan and Givens, 1999;Demirel and Givens, 2000a), allowing the metals to deposit and interact directly on coal surfaces. Dispersed catalysts are reported to give higher liquid yields and require lower catalyst loadings than do supported catalysts Givens, 1998, 2000a, b;Ni et al, 1994).…”
Section: Reducing Capital Costs With Improved Catalystsmentioning
confidence: 99%
“…Because aryl ethers cleave in H20 at high temperature above 315 "C through ionic mechanism [5], this ionic effect of H 2 0 on the cleavage of C-0 bond in DNE is investigated. Even though water alone has inhibition effect on conversion of DNE as described above.…”
Section: One-step Reactionmentioning
confidence: 99%
“…Mikita and Fish (1986) suggested that water acts to open new ionic reaction pathways through its solvation effect. In a later study, Ruether et al (1987) investigated hydroliquefaction coal conversion in the presence of catalysts and found that highest conversions are obtained without added water. They concluded that for reaction systems with the catalyst deposited from solution onto the coal particles, the resultant particles are highly reactive and that water retains a role as a solvent for the catalyst.…”
Section: H20-d0 Exchanpe Studies On Coalsmentioning
confidence: 99%